Vacuum Filtration‐and‐Transfer Technique Helps Electrochemical Quartz Crystal Microbalance to Reveal Accurate Charge Storage in Supercapacitors. Issue 11 (15th May 2019) - Zhang, Qingnuan; Levi, Mikhael D.; Chai, Yinguang; Zhang, Xu; Xiao, Dewei; Dou, Qingyun; Ma, Pengjun; Ji, Hengxing; Yan, Xingbin
Abstract: Electrochemical quartz crystal microbalance (EQCM) can be used to study the charge storage mechanisms of supercapacitors because of its excellent accuracy in mass change, and a homogeneous and ultrathin sample coating is strongly required for accurate measurement. However, it is difficult to obtain such a coating by the frequently used methods. Here a vacuum filtration‐and‐transfer (VFT) technique is reported to achieve this target. To prove the universality of this method, six materials with different dimensions are selected as research objects, and they are prepared into test films on quartz by VFT method and well‐used spray method for EQCM measurements, respectively. The results show that the VFT method can eliminate the influence caused by inhomogeneity of the films, which is beneficial for clearly distinguishing the rigid model from the viscoelastic model. This method helps EQCM to reflect more precise quality change as well as deformation of the material itself. Consequently, it makes EQCM more reliable to describe the energy storage mechanisms of various electrode materials. Abstract : A novel vacuum filtration‐and‐transfer (VFT) technique for the sample preparation of electrochemical quartz crystal microbalance (EQCM) is demonstrated. Compared with the frequently used spray method, the VFT method can effectively reduce the change of resonance width caused by sample inhomogeneity, thereby making EQCM more reliable to describe the energy storage mechanisms of various electrode materials.